Experimental Study of the Durability of Cutting Tips Prepared via Powder and Casting Metallurgy - Monka, Peter; Monkova, Katarina; Sykorova, Libuse; Novak, Martin (Manufacturing Technology Journal, 2018)
Machining has long been the most used technology in manufacturing processes. On the other hand, new materials are being developed or new ways of preparing them are being developed. One of such materials is High Speed Steel (HSS). The article deals with experimental study of a cutting tool durability prepared via powder and casting metallurgy. Durability of cutting tips produced from HSS Vanadis 30 (SN 41 9830) were tested during the short-term radial tests. Three modifications of the HSS steel were studied, while two types of them were prepared via powder metallurgy and the third one was made via casting metallurgy. The measured values were statistically processed and submitted to the remoteness testing according to Grubbs. The results have shown that the most appropriate material for production of cutting tips, ranked based on three studied steels from the durability point of view, appears Vanadis 30 produced via powder metallurgy alloyed by component Nb.
Keywords: durability; cutting tip; high speed steel; metallurgy; lathe-turning test